Transforming Population Data Governance through PivotTables and Digital Archiving in Pagarbatu Village, North Tapanuli - Yulia Kurni Sari Sitepu; Rony Marpaung; Limmarten Simatupang; Diana Martiani Situmeang; Dostri Ambarita; Jontinus Manullang; Jonas Franky R Panggabean; Veronika H Purba (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Digital transformation at the village-government level is essential for improving administrative efficiency, data accuracy, institutional accountability, and public information services. Pagar Batu Village, Sipoholon District, North Tapanuli Regency, covers an area of approximately 17.49 km² and is administered by only five village officials. Prior to this community engagement program, population records had been maintained using basic Microsoft Excel worksheets, while document storage lacked standardized classification, file-naming conventions, access restrictions, and systematic backup procedures. This program aimed to strengthen the capacity of village officials to manage, summarize, store, and retrieve population data through the use of Microsoft Excel PivotTables and a structured digital archiving system. The program was implemented through needs assessment, data standardization, preparation of learning materials, hands-on demonstrations, guided practice, product-based assignments, evaluation, and follow-up assistance. The outputs included a standardized population database template, automated population summaries, a classified digital archive structure, file-naming guidelines, access-level classifications, and an operational guide. The program demonstrated that optimizing familiar and readily available digital tools can provide a practical approach to improving population data governance in a village with limited human and technological resources. This initiative contributes primarily to Sustainable Development Goal 16 by supporting effective, accountable, and transparent local institutions, while also contributing to SDGs 4 and 9 through digital capacity development and administrative innovation.